2017
DOI: 10.1137/15m103830x
|View full text |Cite
|
Sign up to set email alerts
|

On Viscosity Solution of HJB Equations with State Constraints and Reflection Control

Abstract: Abstract. Motivated by a control problem of a certain queueing network we consider a control problem where the dynamics is constrained in the nonnegative orthant R

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The condition that h ′ i (t) ≥ 0 a.e. on R can be stated that h i is nondecreasing on R. In [2], the authors have studied the nonlinear elliptic partial differential equation (1.2) F (D 2 u, Du, u, x) = 0 in Ω := (0, ∞) n , with the nonlinear Neumann type boundary condition, similar to the above, stated as…”
Section:     mentioning
confidence: 99%
See 3 more Smart Citations
“…The condition that h ′ i (t) ≥ 0 a.e. on R can be stated that h i is nondecreasing on R. In [2], the authors have studied the nonlinear elliptic partial differential equation (1.2) F (D 2 u, Du, u, x) = 0 in Ω := (0, ∞) n , with the nonlinear Neumann type boundary condition, similar to the above, stated as…”
Section:     mentioning
confidence: 99%
“…As shown in [2], the boundary value problem (1.2)-(1.3) arises in a scaling limit of stochastic control of queuing systems. A main contribution in [2] is that, under suitable hypotheses, the value function of the stochastic control problem, obtained in the scaling limit, is identified as the unique viscosity solution of (1.2) and (1.3), with an appropriate choice of F . This identification result heavily depends on the uniqueness or comparison theorem for viscosity solutions, subsolutions, and supersolutions of (1.2)- (1.3).…”
Section:     mentioning
confidence: 99%
See 2 more Smart Citations
“…A legitimate question for these processor sharing type model is that whether the GPS type policy is optimal or not for the pay-off function considered above. Motivated by this question a similar control problem is considered in [14] for a queueing model with finitely many servers and it is shown that the value function associated to the limiting controlled diffusion model solves a non-linear Neumann boundary value problem. The solution is obtained in the viscosity sense and therefore, it is hard to extract any information about the optimal control, even for the diffusion control problem.…”
Section: Introductionmentioning
confidence: 99%